Kedudukan Perempuan Dalam Penentuan Mahar Menurut Madhab Syafi'i Dan Madzab Hanafi - Abdul Halim; Achmad Lubabul Chadziq (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
According to the Shafi school of thought, the concept of dowry does not burden the groom. Likewise, Article 31 KHI explains that the determination of a dowry is based on the principle of ease and simplicity recommended by Islam. However, sometimes there are prospective brides who ask or decide how much dowry should be given to them. Which can create difficulties for the groom-to-be. Unlike the Shafi'i school of thought, the Hanafi school of thought also has its own opinion. This study uses a qualitative method with a type of literature. While data collection techniques by reviewing, researching, understanding and analyzing literature, documents, which are then analyzed using comparative methods to draw valid conclusions. the conclusion shows that in the Shafi'i and Hanafi schools of thought, any item or object that may be used as a medium of exchange, whether in the form of goods or benefits, may also be used as a dowry or dowry. According to the Shafi'i school of thought, there is no definite stipulation on how much or how little the dowry is, but the sunnah is a minimum of 10 dirhams and a maximum of 500 dirhams. Meanwhile, according to Imam Hanafi, the minimum dowry is the same as the amount of stolen property that the thief must cut off his hand, which is 10 dirhams or 1 dinar. Meanwhile, the position of a woman in determining the dowry is a woman's right that must be paid by a man as proof of the seriousness of her love and affection.